Each side chain of cyclosporin A is not essential for high passive permeability across lipid bilayers. Issue 12 (13th March 2023) - Ono, Takahiro; Tabata, Kazuhito V.; Noji, Hiroyuki; Morimoto, Jumpei; Sando, Shinsuke
Abstract : Cyclosporin A showed lipid bilayer permeability even after the deletion of a side chain. Abstract : We compared the passive permeability of cyclosporin A (CsA) derivatives with side chain deletions across lipid bilayers. CsA maintained passive permeability after losing any one of the side chains, which suggests that the propensity of the backbone of CsA is an important component for high passive permeability.